Pemberdayaan dan Pendampingan Ekonomi Pesantren An-Nur Semanding Tuban Jawa Timur - M. Fathor Rohman; Ahmad Afan Zaini; Siswadi Siswadi; Izzatus Tsani M.; Ahmad Rofi'i; Khoirun Nisa (KERIS : Journal of Community Engagement, 2022)
The activities of students in Islamic boarding schools are not only about matters of worship rituals. Not only carrying out activities that include spiritual aspects such as learning the Koran, praying and others. There are other aspects that also contribute to building activities in Islamic boarding schools, namely economic activities. These economic activities are in the form of community empowerment and assistance that have an impact on the surrounding community, especially empowerment in the economic field. As done by Pondok Pesantren An-Nur Semanding Tuban. Economic empowerment here is in the form of distributing bottled mineral water. Mineral water is packaged in a container which is then labeled 'AINUR' (an acronym for Air Asli Sendang Pancur) which is a spring owned by An-Nur Islamic Boarding School located in Sendang Pancur Village, Semanding District, Tuban Regency, East Java. This is because the environment in the Islamic boarding school has abundant assets and potential water resources. In addition, human resource assistance (students) is also needed. To empower these assets and potentials, assistance is needed starting from the production mechanism to the distribution process that involves the surrounding community. Assistance is carried out using the Asset Based Community Development method or better known as the ABCD mentoring method. By using the ABCD mentoring method which includes: Preparing (preparation); Discovery (find); Dream (future dream); define (map/define assets); Design (designing/connecting and mobilizing assets/action planning) and Destiny (conducting monitoring) can be used as a basis or reference in the process of mentoring and community empowerment in developing the pesantren economy.